The Supplementary Material Used by English Teachers for Teaching Eleventh-Grade Students in SMAN 4 Banjarmasin - M. Fahrurraji; Noor Eka Chandra (ELITE JOURNAL, 2023)
ABSTRACT Supplementary materials are needed as additional materials for teaching English. This study was conducted to discover detailed information on what supplementary materials were used and how they were implemented by English senior high school teachers. The approach of this study was descriptive qualitative. The subject of this research was two English teachers SMAN 4 Banjarmasin. The primary data was collected through observation, while secondary data was collected through interviews and documentation. This research showed three materials teachers often use as supplementary material to be implemented while teaching in the form printed, visual and internet-based. Printed supplementary materials in the form of workbooks. Meanwhile, supplementary internet-based materials in the form of selected internet-based material and YouTube video. It is suggested that teachers consider the criteria for selecting teaching-learning material before implementing the supplementary material in the classroom. It is also recommended for further research focus more on how students respond to the implementation of supplementary materials by the English teacher in the classroom. Keywords: descriptive qualitative, supplementary material, English teaching